The Social Media Da’wah and Language Use: A Comparative Study of Indonesian Islamic Figures - Cahyawati, Octaviani Dwi Indah; Subagio, Moch. Rouf Raditya; Haqie, Muhammad Laix; Swasono, Endratno Pilih (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This research examines the use of language in the context of Islamic da’wah delivered by Indonesian Islamic figures through social media such as YouTube and TikTok. This research aims to (1) identify the types of speech acts used by each figure, (2) analyze the figurative language style used, and explore the situational influence on the applied da’wah communication strategy. This research used a descriptive qualitative method with a sociopragmatic approach, and data were obtained from 16 selected videos featuring four Islamic figures: Ahmad Anwar Zahid, Felix Siauw, Husein Ja’far Al Hadar (Habib Ja’far), and Husain Basyaiban (Kadam Sidik). The study results show that the most frequently used speech acts are directive, assertive, and expressive, which focus on commands or invitations, conveying facts, and emotional expressions. Figurative language styles such as similes, metaphors, personifications, and hyperboles are also often used to strengthen the rhetorical power of da’wah. This research concludes that the effectiveness of da’wah in digital media depends on linguistic strategies that are adjusted to the platform, context, and characteristics of the audience. These findings contribute to further understanding of religious communication and support the development of contextual da’wah strategies in the digital era.